WOMEN’S WORLDVIEW IN WARTIME: A GENETIC STRUCTURALIST READING OF ZOULFA KATOUH’S AS LONG AS THE LEMON TREES GROW - Ninik Hardianti; Nurholis Nurholis; Udayani Permanaludin (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study examines the women’s worldview in Zoulfa Katouh’s novel As Long as the Lemon Trees Grow. The research aims to analyze how the experiences of war shape female consciousness through the character of Salama Kassab. This study applies Lucien Goldmann’s genetic structuralism, which views literary works as expressions of collective consciousness shaped by socio-historical conditions. Using a qualitative descriptive method, the analysis focuses on narrative excerpts that illustrate women’s psychological and social experiences during the Syrian civil war. The findings reveal four major aspects that construct the women’s worldview in the novel: despair and emotional exhaustion, trauma and psychological fragmentation, shattered dreams and disrupted futures, and moral conflict between survival and humanitarian responsibility. These aspects demonstrate how prolonged conflict transforms women’s identities, aspirations, and ethical perspectives. Salama’s experiences reflect not merely an individual struggle but the collective condition of women living in war-affected societies, where caregiving responsibilities, psychological trauma, and moral dilemmas become part of everyday survival. Through the lens of genetic structuralism, the novel articulates a collective female consciousness shaped by violence, displacement, and social collapse. This study contributes to the limited scholarship on women’s collective consciousness in wartime literature by extending Goldmann’s framework into gendered conflict analysis.